A New Control Method of Hybrid Step Motors For Educational and Industrial Applications Using Visual Basic 6 0 - AKÜNER, MUSTAFA CANER (My University, 2006)
This paper is carried out to enhance a useful computer program for digitally controlled hybrid step motors (HSM); application of computer program to perform the analysis of operation values for HSM such as number of steps, angular way, motor speed; and advanced use of that digitally programmed HSM in industrial applications. This program provides an algorithm including the command strategy of parallel ports for the control of HSM; presents a user-friendly software package developed in Visual Basic and enables to combine numerical computations and graphical illustrations. This advanced package can be used for the other motor control systems with a little change in the source of the program in any educational (technical education, electricity-electronics and computer engineering) and industrial application areas.
Keywords: Hybrid step motors; Visual basic; Digital control; Parallel port